Factors Associated with Postacute COVID-19 Syndrome Among Patients in Malaysia - Ballasingam, Ahtheemathurra; Islahudin, Farida; Abdul Aziz, Siti Azdiah; Makmor-Bakry, Mohd (UI Scholars Hub, 2023)
Background: Post-acute COVID-19 is known to affect multiple organs. It is essential to determine factors that affect post-acute COVID-19 syndrome and medications needed by patients for optimized care. Methods: A prospective cohort study was conducted among patients recruited by stratified sampling from two COVID-19 hospitals in Malaysia. Patients were followed up for 6 months using a standard questionnaire to identify demographics, symptoms, medications taken, and factors associated with post-acute COVID-19 syndrome. Results: A total of 388 were successfully followed up. The most frequently reported symptom was respiratory symptoms (N = 168, 43.30%), of which cough (N = 134, 34.54%) was the most common. After 12 weeks of follow-up, respiratory syndrome (N = 56,14.43%) was frequently reported, of which cough (N = 41, 10.57%) was the most common. For respiratory syndrome, patients were commonly managed with diphenhydramine cough suppressants (N = 6, 1.55%, month 4) and metered dose inhaler (MDI) salbutamol (N = 7, 1.8%, month 4). The risk factors for post-acute COVID-19 syndrome were increased by 1.02 times (95% CI: 1.01, 1.04) with each advanced year of age and 2.87 times (95%CI: 1.51–5.48) in the presence of co-morbidities. Conclusions: Post-acute COVID-19 causes multiorgan involvement, and symptoms may remain for months, with patients taking various medications. Patients with risk factors should be monitored closely for post-acute COVID-19 symptoms.